Population structure of montane bamboo and causes of its decline in Echuya Central Forest Reserve, South West Uganda - Bitariho, Robert; McNeilage, Alastair (African Journal of Ecology, 2007)
Montane bamboo is of immense importance to the people living adjacent to Echuya Forest Reserve. It is used for building poles, bean-staking and basket weaving. The bamboo in Uganda occurs mostly in protected areas. Over the past 50 years, the bamboo forest cover has been declining. This study aimed at determining bamboo density and distribution and the possible causes of its decline within Echuya. We used exploratory inventories, bamboo assessment plots and village interviews to determine bamboo population structure and possible causes of its decline in Echuya. Bamboo forest decline in Echuya may be blamed on several factors that interplay together. Poor harvest methods especially during the clear cutting of bamboo for bean-stakes and stakes for house wefts seems to be the remote cause of the bamboo forest decline. Other causes for the bamboo forest decline are damages caused by insect borers and climber loads on the bamboo stems. The remote causes have been exacerbated by the invasion of secondary forest tree species such as Macaranga kilimandscharica that have slowly taken over areas previously occupied by the bamboo forest. Seventy per cent of the local people interviewed agree that over-harvesting of bamboo is the major reason for its decline
Keywords: Bamboo strata; Echuya forest; Montane bamboo